Renewable Energy Projects are “Green” to the Nature, but Not Always to the People? An Observation-based Study from Chile - Rana, Md Sohel (Journal of Bangladesh Institute of Planners, 2019)
This paper describes a grounded theory-based research with a view to theorizing local community people’s attitudes towards renewable energy generation projects. The study is conducted in the context of southern rural areas of Chile that has been receiving number of hydroelectricity-based renewable energy generation projects in recent years. Under the broad framework of grounded theory, the study is designed with an actor-oriented approach availing local knowledge as the research vehicle with a view to exploring local realities. The thematic abstraction, in inference, reveals three sets of drivers that affect local community people’s attitude and action-building towards such projects. The paper avails a story-telling manner to explain the step by step process of abstracting those drivers from qualitative data. JBIP, Vol. 12, 2019 (Printed in June 2020), pp. 21-32